Cutting a Long Story Short? The Clinical Relevance of Asking Parents, Nurses, and Young Children Themselves to Identify Children's Mental Health Problems by One or Two Questions. (31st December 2014) - Borg, Anne-Mari; Salmelin, Raili; Joukamaa, Matti; Tamminen, Tuula
Abstract : Background and Aims . Assessing young children's mental health is a crucial and challenging task. The aim of the study was to evaluate the clinical relevance of asking parents, nurses, and young children themselves to identify children's mental health problems by only one or two questions. Methods . In regular health check-ups of 4- to 9-year-old children ( n = 2682 ), parents and public health nurses assessed by one question whether the child had any emotional or behavioral difficulties. The child completed a self-evaluation enquiry on his/her emotional well-being. A stratified proportion of the participating parents were invited to a diagnostic interview. Results . Sensitivities were fairly good for the parents' (68%), nurses' (65%), and their combined (79%) one-question screens. Difficulties identified by parents and nurses were major risks (OR 10–14) for any child psychiatric disorders ( P < 0.001 ) . The child's self-evaluation was related to 2-fold to 3-fold risks ( P < 0.05 ) for any psychiatric diagnosis, for any emotional diagnosis, and for negative situational factors. Conclusion . The one-question screen for parents and public health nurses together quite adequately identified the young children with mental health problems. The child's self-evaluation provided relevant and complementary information on his/her mental health and especially emotional problems.